The impact of vitamin D on atopic disorders: assessing evidence for a causal relationship - Zúñiga, Valeria Andrea; Bazan-Perkins, Blanca (Frontiers in Nutrition, 2025)
Since the beginning of COVID-19 pandemic, there has been a noticeable increase in the consumption of vitamin D. Evidence accentuates the generation of a pro-tolerogenic T helper 2 cell state with vitamin D, suppressing T helper 1 inflammatory response. T helper 2 cell polarization is characteristic of atopy. However, although the literature on vitamin D and atopy has yielded controversial results, multiple studies have described an inverse relationship between vitamin D levels and the severity of atopy, as well as an improvement of the pathology with vitamin D supplementation. A different approach is offered in the analysis of the immunological mechanisms by which vitamin D acts in the human body, supporting its use as a promoter of homeostasis. In this sense, vitamin D promotes a balanced state through the action of regulatory T cells, controlling cytokines, both pro- and anti-inflammatory, and by reducing B cell prolif eration and differentiation, thus preventing the possible development of atopy.